Algorithm of Encrypting Digital Image Using Chaos Neural Network - Ying Mao (Advances in Multimedia)
With the rapid development of digital communication technology, data and image encryption methods will get more and more in-depth research in these aspects. Although the original cipher method can keep the image confidential, because of the storage method of the image data, for the image with too high pixel value, the process of keeping the two-dimensional information confidential and decoding will bring a large amount of computation, and the accuracy of encryption and decryption cannot be guaranteed. This paper presents a visual image encryption algorithm based on the compressed sensing method of the Hopfield chaotic neural network. Different from the existing visual image encryption methods, our method can directly embed the noise like information after encryption into the alpha channel of the carrier image, thus increasing the visual stability of the computer. Finally, through the comparison and analysis of simulation experiments, we find that the image encryption algorithm proposed in this paper has the advantages of wide password space, low risk, good visual stability, good decoding effect, and good robustness.